PERTANGGUNGJAWABAN PIDANA DALAM PEMALSUAN SURAT TERHADAP PERJANJIAN KREDIT (STUDI KASUS PUTUSAN NOMOR: 952/PID.B/2019/PN.JKT.BRT) - Deasy Diantirta Ayu; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2021)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit or other forms in order to improve the standard of living of the people. Therefore, it is very necessary to know the legal consequences of the credit agreement with the presence of a forged letter and criminal liability for the decision of the district court number: 952/Pid.B/2019/PN.JktBrt. Furthermore, the research method used by the author is normative research. According to the results of the author's analysis of the legal consequences of the credit agreement with the existence of a forged civil letter, the agreement can be said to be null and void because in making a credit agreement you must use an authentic deed, identity and other original documents, not fake ones. In the verdict number 952/Pid.B/2019/PN.JktBrt the charges used by the judge are alternative charges, namely: the first indictment of the defendant is subject to Article 263 Paragraph (2) of the Criminal Code in conjunction with Article 55 Paragraph (1) of the 1st Criminal Code and the second indictment the defendant is subject to Article 378 of the Criminal Code jo. Article 55 Paragraph (1) 1st of the Criminal Code.